2012
DOI: 10.1098/rstb.2011.0162
|View full text |Cite
|
Sign up to set email alerts
|

A word in the hand: action, gesture and mental representation in humans and non-human primates

Abstract: The movements we make with our hands both reflect our mental processes and help to shape them. Our actions and gestures can affect our mental representations of actions and objects. In this paper, we explore the relationship between action, gesture and thought in both humans and non-human primates and discuss its role in the evolution of language. Human gesture (specifically representational gesture) may provide a unique link between action and mental representation. It is kinaesthetically close to action and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 135 publications
4
94
0
6
Order By: Relevance
“…It has been proposed that gesture and speech form a single system of communication, because they are linked to the same thought processes, even if expressed differently (Arbib et al , 2008, Cartmill et al , 2012, Eisen et al , 2014b. Observing and executing the grasp of small and large objects, for example a grape versus an apple, changes the degree of mouth opening and simultaneously pronunciation of syllables (Gentilucci et al , 2008b).…”
Section: Mirror Neurons In Language and Gesturementioning
confidence: 99%
“…It has been proposed that gesture and speech form a single system of communication, because they are linked to the same thought processes, even if expressed differently (Arbib et al , 2008, Cartmill et al , 2012, Eisen et al , 2014b. Observing and executing the grasp of small and large objects, for example a grape versus an apple, changes the degree of mouth opening and simultaneously pronunciation of syllables (Gentilucci et al , 2008b).…”
Section: Mirror Neurons In Language and Gesturementioning
confidence: 99%
“…B 369: 20130295 that the analogue information must be conveyed in the manual modality. The manual modality may be privileged when it comes to expressing emergent or mimetic ideas, perhaps because our hands are an important vehicle for discovering properties of the world [98][99][100].…”
Section: (Iv) Narrativesmentioning
confidence: 99%
“…Acceptance of personal events may be supported by bodily movements, as bodily positions and movements can act as symbolic cues to memory and support the holding of information and experiences in conscious awareness (i.e., in working memory). In support of this, it has been shown that working memory performance can improve if bodily gestures are also utilized to aid in imprinting memories (Cartmill, Beilock, & Goldin-Meadow, 2012).…”
Section: International Journal Of Transpersonal Studies 17 Managing Wmentioning
confidence: 99%